Computer Intellectual Property Claims: Computer Software and Data Base Protection - Michael S. Keplinger (Washington University Law Quarterly, 1977)
The National Commission on New Technological Uses of Copyrighted Works has defined a set of subsidiary issues which have formed the basis for conducting its research and study activities. These issues include: (1) The manner in which computer software should be dealt with by copyright law; (2) How the copyright law should apply to automated data bases; (3) The copyright consequences of the input or output of a copyrighted work within a computer system; (4) The copyright status of “new works of authorship” created by the application or intervention of computer technology; and (5) How the law should deal with the long range implications of photocopying and other means of replication of copyrighted works. Keplinger explains the activities of the National Commission on New Technological Uses of Copyrighted Works, which was established in 1974 to recommend to the President and Congress changes in the copyright laws necessitated by advancing computer technology. Carefully striking a balance between the public interest and that of the creator of a work, the commission’s proposal precludes the unauthorized input, output, or storage of a work within the memory components of a computer system while specifically prohibiting copyright protection for ideas, procedures, principles, discoveries, or concepts.
Keywords: Copyright